An Analysis the Financial Performance of BAZNAS - Tri Wulandari; Rofiul Wahyudi (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2023)
This research aims to measure and analyze the financial performance of the Klaten Regency National Amil Zakat Agency in 2019-2022. Performance measurement in this research uses the efficiency ratio, amil fund ratio and growth ratio issued by BAZNAS. Data obtained from the Klaten Regency BAZNAS financial report for 2019-2022. Research data collection techniques use observation and documentation techniques. The method in this research is descriptive quantitative using simple linear regression analysis. Model testing was carried out with SPSS version 25.0 software. Statistical testing in this research uses the classic assumption test which consists of the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Then proceed with the R2 coefficient of determination test. The results of statistical analysis have fulfilled most or all of the relevant classical assumptions. Meanwhile, the results of the analysis of the coefficient of determination (R2) are 0.564 or 56.4%, which explains that the Ratio variable (Efficiency, Capital Funds and Growth) has an influence on the dependent variable of financial performance effectiveness, while the remaining 43.6% is caused by other factors.